Dinamika Pergerakan Bayangan Matahari dalam QS. An-Nahl Ayat 48 dan Relevansinya terhadap Penentuan Arah Kiblat: Kajian Tafsir Jami’ Al-Bayan Karya Al-Thabari - Filza Syahira; Adenan (Aksioreligia, 2026)
This study examines the dynamics of solar shadow movement in QS. An-Nahl verse 48 through tafsir ilmi, focusing on Ibn Jarir Al-Thabari’s interpretation in Jami’ al-Bayan and its relevance to qibla direction determination in Islamic astronomy. Previous studies on qibla direction have mostly emphasized technical-astronomical and normative-juridical aspects, while the integration of Qur’anic exegesis and astronomical practice remains limited. This study aims to analyze Al-Thabari’s interpretation of QS. An-Nahl verse 48, examine its relevance to contemporary qibla methods, and formulate an integrative framework between tafsir ilmi and ilmu falak. Using qualitative library research, this study relies on Jami’ al-Bayan as the primary source and contemporary Islamic astronomy literature as secondary sources. The findings show that yatafayya’u zhilaluh provides a strong linguistic and epistemological basis for understanding shadow movement. This interpretation supports rashdul qiblah as an applicable method connecting revelation and science within the broader tradition of Islamic scholarly integration today.